Islamic Marketing Aspects in View of Consumer Impulse Shopping Behaviour on Fashion Products on Social Media Tiktok Shop - Arifin, Rois; Taqwiem, Ahsani (ITB AAS INDONESIA Surakarta, 2024)
This research uses a qualitative descriptive method with a case study approach in analyzing things that happen to the scope of the research subject, and can also be used to describe how related research works. Data collection techniques carried out by researchers by means of interviews, observation and documentation. The results of this study are; first, the affiliate marketing business on tiktok is a new business model which is a digital business that is currently viral among millennials, with the convenience offered by tiktok it makes it easy for tiktok users to join affiliate marketing, but must still follow the terms and conditions imposed by tiktok. Apart from that, you should also do business with your heart and follow the example of sharia marketers in the style of the Prophet Muhammad, who is known as al Amin (trustworthy). As for suggestions and recommendations for affiliates in doing business, both on social media, TikTok and other media, so that they put heart and knowledge first in doing marketing, not to be tempted by instant results, as much is offered in content on social media. Marketing or reviewing a product, in addition to paying attention to the law of the goods being sold, also pays attention to ethics in marketing the product. As well as always studying the development of social media and digital business models so that they remain consistent and don't miss the latest information